The Legal Responsibility of Employers for Paying Wages of Workers who are Temporary Layoffs During the COVID-19 Pandemic - Avita Gayatri Kresnapratiwi (Nurani Hukum, 2021)
The COVID-19 pandemic has an impact on the economic downturn in every company, so many companies choose to temporary layoffs their workers. In the case of wages for workers who are temporary layoffs, employers are not allowed to not pay wages while the workers are temporary layoffs, so if the employer is unable to pay the workers' wages according to the minimum wage, the employer can postpone the payment of wages, but must first negotiate with the workers/laborers or labor union. For this reason, this article was written with the aim of knowing the responsibility of employers when temporary layoffs workers during the COVID-19 pandemic. The type of research used by the author in this study is normative juridical research, using descriptive analysis using library data as the main data. The results of this study can be concluded that the act of temporary layoffs workers was chosen by the employer as an effort to anticipate the occurrence of termination of employment. The responsibility of employers if they do not pay full wages to their workers during the COVID-19 pandemic employers can be fined, as regulated in Article 55 paragraph (1) of Government Regulation Number 78 Year 2015 concerning Manpower Wage, whereas for workers because their wages are not paid, they can file a termination between the worker and the employer because employers do not pay wages on the promised time for 3 consecutive months or more and do not do what has been promised.